Recent Trends in M&A of Japanese Firms and Corporate Governance (Malaysian Management Journal, 1997)
It is said that we are in the middle of a second boom of mergers and acquisitions in Japan. After the collapse of the bubble economy, many failed companies have been rescued by viable companies through mergers. At the same time, the number of owner-managers looking for successors by way of being acquired increased. Almost all of them are owners of small and medium companies. In addition, for diversification, Japanese companies have come to rely upon 'mergers and acquisitions (M&A) more frequently than before. The second M&A boom in Japan implies that Japanese business people have learned how to use M&A techniques for corporate restructuring as well as corporate growth, through the experiences of cross-border M&A activities in the 1980s. New trends in cross-border M&A of Japanese companies emerged. For example, foreign direct investments by Japanese companies shifted away from Asia towards the US and Canada in the 1980's. Investment in the US and Canada increased to as much as half of all of the direct foreign investments by the Japanese, compared with the previous level of one third. Subsequently, starting around 1989, the number of acquisitions in Europe surged, presumably due to the unified markets in Europe. The Japanese corporate governance system which became active after the collapse of the bubble economy in, Japan, remarkably reduced the need to use takeovers and acquisitions as a disciplinary mechanism; this contrasts- sharply with the way business is conducted in the US. Acquiring or merging with another company was an option only when the survival of an important business relationship is jeopardized by financial distress or loss in competitiveness. The bubble economy has brought excess cash for management. Therefore, decisions about how to allocate cash bring sharp disagreements among stakeholders about the future direction of the company. Japanese managers who are virtually free from shareholders' control have pursued Zeiteku activities (financial engineering), making use of cash in hand and low-cost funds procured in the capital market. The results turned out to be a total failure when the bubble burst. Managers in declining industries are pushing to restructure companies in the direction of product or business diversification. Implicit promise of employees' life-long employment and corporate growth are the main motives of their strategies. The behaviour of Japanese managers suggests that freedom from capital market discipline prompted them to benefit themselves and the employees of the firm at the expense of other stakeholder interests. The remarkable success of Japanese companies in the postwar period has furnished the Japanese corporate governance system with a unique market for corporate control. Experience and knowledge obtained after the collapse of the bubble economy will create a different market for corporate controlâ€”a market which brings more challenge to incumbent management since there is a greater chance of hostile bids by outsiders.